Factors Influencing Timely Syllabus Coverage in Public Secondary Schools: Teachers’ Perception i n Migwani Sub - County, Kitui County, Kenya - Mulwa, David Musyoki; Mutia, Peter Mbalaka (Journal of Educational Policy and Entrepreneurial Research, 2016)
The purpose of this study was to establish the extent to which teachers’ related factors (communication, conflict resolution, coordination and attitude) influence timely syllabus coverage in public secondary schools. The objectives of this study were: to establish the influence of communication on timely syllabus coverage, to establish the influence of conflict resolution on timely syllabus coverage, to establish the influence of coordination on timely syllabus coverage and to establish the influence of attitude towards relational interaction among teachers on timely syllabus coverage in public secondary schools in Migwani SubCounty, Kenya. The study was carried out in Migwani sub county, Kitui County. The study adopted descriptive survey research design. The target population was 285 ordinary teachers in public secondary schools in Migwani Sub-County. A random sample of 128 assistant teachers was selected for the study. A questionnaire was used as the instrument of data collection. Piloting was done in two schools and the pilot test for the research instruments using Pearson’s Product Moment Correlation Coefficient (PPMCC) was found to be 0.9145 for the questionnaire (TQ). Quantitative information was summarized into frequency tables, percentages and graphs. Both descriptive and inferential statistics were used to analyze the data. Descriptive statistics analysis showed Means that indicate that respondents agreed that teacher relational factors have positive influence on timely syllabus coverage. Analysis of variance (ANOVA) test confirmed that all the four teacher relational factors have significant effect on timely syllabus coverage F(dfB, dfW) = F(4, 113), (p < 0.05), and hence all the four null hypotheses were rejected. Pearson moment correlation coefficient test established that there exists a positive correlation between teachers’ relational factors and timely syllabus coverage. The study recommends that teachers interact in a relational manner for this would boost the prospects of timely syllabus coverage.
Keywords: Attitude; Communication; Conflict Resolution; Coordination; Timely syllabus coverage